2000
DOI: 10.1111/j.1528-1157.2000.tb01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Recorded from Pediatric Epilepsy Surgery Patients with Cortical Dysplasia

Abstract: Summary:Purpose: Cortical dysplasia (CD) is a common pathological substrate in patients with early-onset childhood epilepsy. In CD tissue, little is known about the mechanisms responsible for cellular hyperexcitability. In this study, we report initial electrophysiological and morphological observations from normal and dysmorphic cells in pediatric CD patients.Methods: Neocortical "most" and "least" epileptogenic areas were sampled based on neuroimaging and electrocorticography from 15 CD patients (ages 0.3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 21 publications
3
51
0
1
Order By: Relevance
“…Recent studies from our laboratory using in vitro cellular electrophysiologic and anatomic techniques have provided support for both the 'epileptic' neuron and circuit hypotheses in pediatric CD tissue Andres et al, 2004;Cepeda et al, 1999Cepeda et al, , 2003Mathern et al, 2000]. Using voltage-clamp recording techniques, we found that when cytomegalic neurons were depolarized they generated large oscillatory voltage-gated calcium spikes.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies from our laboratory using in vitro cellular electrophysiologic and anatomic techniques have provided support for both the 'epileptic' neuron and circuit hypotheses in pediatric CD tissue Andres et al, 2004;Cepeda et al, 1999Cepeda et al, , 2003Mathern et al, 2000]. Using voltage-clamp recording techniques, we found that when cytomegalic neurons were depolarized they generated large oscillatory voltage-gated calcium spikes.…”
Section: Introductionmentioning
confidence: 94%
“…Evidences from in vitro studies show that cytomegalic neurons are primary epileptogenic cells, whereas "balloon" cells are electrophysiologically inactive 38,43 . FCD are probably not a single entity.…”
Section: Focal Cortical Dysplasiamentioning
confidence: 99%
“…Six cytomegalic interneurons were aspiny or sparsely spiny and 2 were spiny. The number of primary dendrites (8,9) in cytomegalic interneurons was significantly increased compared with that in normal interneurons from non-CD (p G 0.006) and CD (p G 0.033) cases (ANOVA, followed by Bonferroni t-test). Dendritic spines (average 13 T 3/30 Km) were more abundant than in normalappearing interneurons (8 T 2 spines), but the difference was not statistically significant (p = 0.8).…”
Section: Interneuron Cell Morphologymentioning
confidence: 99%
“…Neocortical sample sites were removed for in vitro electrophysiologic and anatomical evaluation based on abnormal neuroimaging and electrocorticography results as previously described (9,11,13). Tissue samples were classified as most abnormal or least abnormal, and, when possible, 2 sample sites were obtained from each patient (7,10).…”
Section: Selection Of Neocortical Sample Sites For Research Studymentioning
confidence: 99%
See 1 more Smart Citation